MICROORGANISMS COLONIZING THE LEAVES, SHOOTS AND ROOTS OF BOXWOOD (Buxus sempervirens L.) - HALINA Kurzawińska; Stanisław Mazur; Jacek Nawrocki (Acta Scientiarum Polonorum: Hortorum Cultus, 2019)
Buxus sempervirens (L.) is an evergreen shrub often used in urban plantings intended for forming the trimmed hedges, as well as for creating geometrical shapes. Its decorative qualities are often diminished by the effects of pathogens colonizing the roots, shoots and leaves. The study was conducted in three consecutive growing seasons. The experimental material originated from a nursery located in southern Poland. The subjects under study were diseased leaves, stems and roots of the boxwood variety ‘Suffruticosa’. Samples consisting of 720 diseased fragments of the shrub were taken for mycological examination. Mycological isolations were performed according to the standard methods used in phytopathology. A total of 1059 colonies of fungi and fungus-like organisms were isolated from the diseased boxwood plants. The fungus Alternaria alternata dominated among all the isolates. The pathogens frequently isolated from the leaves included Macrophoma candollei, Volutella buxi and Fusarium buxicola. Those frequently isolated from the shoots included: Pestalotiopsis sydowiana, Volutella buxi and Fusarium avenaceum. The root system, in turn, was colonized in large numbers by: Fusarium oxysporum, F. avenaceum, Rhizoctonia solani, Botrytis cinerea and Phytophthora cinnamomi. Results of the three-year study show a comprehensive participation of phytopathogens in the disease process affecting the boxwood variety ‘Suffruticosa’.